The association between advanced orthopedic certification and confidence and engagement in prescription opioid medication misuse management practices: a cross-sectional study. (4th July 2022) - Magel, John; Bishop, Mark D.; Lonnemann, Elaine; Cochran, Gerald; Fritz, Julie M.; West, Nancy; Gordon, Adam J.
ABSTRACT: In the United States, attaining the orthopedic certified specialist (OCS) credential or the orthopedic subspecialty credential of Fellow of the American Academy of Orthopedic Manual Physical Therapists (FAAOMPT), may lead to a higher level of orthopedic practice. It is unknown whether attaining these credentials influences physical therapist confidence in and frequency of engagement in prescription opioid medication misuse (POMM) management practices. A national cross-sectional web-based survey of PTs identified whether respondents had an OCS or FAAOMPT credential. Self-report confidence in POMM-related management practices and the frequency of engaging in these practices were assessed. Logistic regression evaluated association between credential status and confidence in, and frequency of, engagement in POMM-related management practices. The analysis included 402 respondents with a mean age of 41.0 (SD = 11.2) and 203 (50.4%) females. There were 91 (22.6%) PTs with a FAAOMPT credential, 143 (35.6%) with an OCS but with no FAAOMPT credential and 168 (41.8%) had neither credential. Compared to those with an OCS credential, FAAOMPTs reported greater confidence in, and greater frequency of engagement in, POMM-related management practices ( p < .05). Compared to those without an OCS or FAAOMPT credential and compared to those with an FAAOMPT credential, those with an OCS did not report greater confidence or greater engagement in any POMM-related management practice ( p ≥ .05). Obtain the FAAOMPT credential may increase PTs' confidence in some POMM-related management practices. Research is needed to determine why FAAOMPTs report greater confidence and engagement in POMM-related management practices.